ELASTISITAS HUKUM ISLAM DALAM MERESPONS PERUBAHAN SOSIAL - Lbs, Junaidi (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2014)
The present paper will describe elasticityof Islamic law in responding global and social change. The Islamic law is not only a law given by the will of Lordto all human being, but it has been also a dynamic and flexible law which came gradually in accordance withdevelopment of muslim societies through ijtihad which interpreteds the sacred text, naş, compares analogicallya new case that there is no legal recommended with a legal recommended case based on the mean of Islamiclaw. Historically, through considering public interest and social change logic, the government has a capableof declaring a decision that has relation to the naş argument by political power if needed. it was followed, forinstance, that a male muslim who was allowed to marry a christian woman was forbidden in Umar bin Khatab era